2018
DOI: 10.3389/fmicb.2018.00516
|View full text |Cite|
|
Sign up to set email alerts
|

Azole-Resistance in Aspergillus terreus and Related Species: An Emerging Problem or a Rare Phenomenon?

Abstract: Objectives: Invasive mold infections associated with Aspergillus species are a significant cause of mortality in immunocompromised patients. The most frequently occurring aetiological pathogens are members of the Aspergillus section Fumigati followed by members of the section Terrei. The frequency of Aspergillus terreus and related (cryptic) species in clinical specimens, as well as the percentage of azole-resistant strains remains to be studied.Methods: A global set (n = 498) of A. terreus and phenotypically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 33 publications
3
61
2
1
Order By: Relevance
“…terreus s.s., A. citrinoterreus and A. hortai are the most common found species in clinically samples [17,21,29]. These three species were found to exhibit highest growth and germination rates at 30°C and 37°C, which might partially explain their high frequency in clinical specimen [17,21,29]. A. terreus s.s. is the most Figure 5.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…terreus s.s., A. citrinoterreus and A. hortai are the most common found species in clinically samples [17,21,29]. These three species were found to exhibit highest growth and germination rates at 30°C and 37°C, which might partially explain their high frequency in clinical specimen [17,21,29]. A. terreus s.s. is the most Figure 5.…”
Section: Discussionmentioning
confidence: 98%
“…A prospective international Aspergillus terreus study revealed that A. terreus s.s. was found to be the most frequently isolated species from clinical specimens (86.8%) followed by A. citrinoterreus (8.4%), A. hortai (2.6%), A. alabamensis (1.6%), A. neoafricanus (0.2%), and A. floccosus (0.2%). Frequencies of cryptic species vary with geographical origin [21]. A French study found similar occurrence of cryptic species [29], suggesting that cryptic species might be underdiagnosed in less experienced centers due to their morphological indifference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If aspergillosis was suspected, the patient was switched from itraconazole to voriconazole. The rationale for this switch is that voriconazole is considered the drug of choice for IA and has better absorption than itraconazole, coupled with the low prevalence of azole‐resistant strains in Israel . Additional antimicrobials included nystatin mouth washes for 1 month, valganciclovir 450 mg daily for 6 months, and trimethoprim/sulfamethoxazole 160/800 mg three times per week.…”
Section: Methodsmentioning
confidence: 99%
“…Aspergillus fumigatus (A. fumigatus) is the most common cause for IA [33,34] and most prior studies have focused on the evaluation of PCR assays for this species. Epidemiology of IA globally varies and species other than A. fumigatus are increasing in prevalence [35]. Additionally, non-Aspergillus molds occur more frequently due to the increasing use of antifungal prophylaxis and more intensive immunosuppressive therapies [36].…”
Section: The Goodmentioning
confidence: 99%